Variation in compressive properties of Indian brick masonry and its assessment using empirical models. (October 2021) - Padalu, Pravin Kumar Venkat Rao; Singh, Yogendra
Highlights: Mechanical characterization of solid clay bricks, mortar cubes and masonry prisms. Stress–strain behaviour of masonry and its constituents is presented. Compressive strength vs elastic modulus relationship of masonry is explored. Variation in mechanical properties of Indian masonry & its constituents is studied. Performance of empirical models in predicting properties of masonry is compared. Abstract: Estimation of basic material properties of masonry and understanding its compressive behaviour is the initial crucial steps in analyzing the performance of masonry buildings. Masonry being a complex and inelastic material has a large variation in mechanical properties such as compressive strength and modulus of elasticity. The variation for Indian masonry is even higher, as most of the manufacturing and construction process is performed manually. Mechanical characterization of solid clay bricks, mortar cubes (1:4 cement-sand proportion) and masonry prisms are performed using laboratory tests to determine the compressive properties. The non-linear stress–strain behaviour of masonry and its constituents is also presented. Based on the results of the present study and past literature, variation in mechanical properties of Indian masonry & its constituents is studied based on two different mortar grades (1:4 and 1:6). It is observed that these properties have a large portion of aleatory variability, due to variations in constituent materials and workmanship. The relationship between the compressive strength and elastic modulus of brick, mortar and masonry is also presented. Further, the relative performance of different empirical models in predicting the properties of masonry is compared and their efficacy is examined using the statistical and error-assessment parameters. Results showed that the compressive strength of the Indian masonry can be determined using most of the empirical relations available worldwide, with reasonable accuracy; however, the elastic modulus of masonry cannot be estimated with the same level of confidence.